PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PEMECAHAN MASALAH MATEMATIKA DI SEKOLAH DASAR - Safitri, Yolanda; Masniladevi, Masniladevi; Harni, Harni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this study was to describe the application of the Problem Based Learning model to improve learning outcomes in solving mathematical problems. This research is Classroom Action Research which uses qualitative and quantitative approaches. The subjects of this study were twenty five teachers and fifth grade students. The implementation of this research was carried out in two cycles with research procedures consisting of planning, implementation, observation and reflection. The results obtainedshowed an increase: 1) RPP cycle I an average value of 78.57% (B), cycle II averaged 91.07% (SB). 2) Implementation of learning based on: a) teacher activities average value 75% (C), cycle II average value 90% (SB), b) student activity average value 65% (C), cycle II average value average of 87.5% (SB). Whereas, 3) Student learning outcomes an average value of 65.06 (C) cycle II an average value of 83.30 (B). Thus, the application of the Problem Based Learning model can improve the learning outcomes of mathematical problem solving in Class V of Padang Besi Elementary School 08 Padang Keywords: Problem Based Learning; Learning Outcomes Problem Solving; Mathematics